1997
DOI: 10.1074/jbc.272.25.15920
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica Promotes Deactivation of Macrophage Mitogen-activated Protein Kinases Extracellular Signal-regulated Kinase-1/2, p38, and c-Jun NH2-terminal Kinase

Abstract: The enteropathogenic bacterium Yersinia enterocolitica counteracts host defense mechanisms by interfering with eukaryotic signal transduction pathways. In this study, we investigated the mechanism by which Y. enterocolitica prevents macrophage tumor necrosis factor-␣ (TNF␣) production. Murine J774A.1 macrophages responded to Y. enterocolitica infection by rapid activation of mitogen-activated protein kinases (MAPK) extracellular signal-regulated kinase (ERK), p38, and c-Jun NH 2 -terminal kinase (JNK). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 71 publications
3
113
0
Order By: Relevance
“…Until recently, four of the six injected effectors of Yersinia were believed to target elements of the cytoskeleton to block phagocytosis. However, recent reports illustrated that some of the anti-phagocytic effectors such as YopH can also interfere with signaling pathways of the immune defense system, leading to a down-regulation of the F c -mediated oxidative burst in macrophages and neutrophils, for example (12,46,47). The caspase-1 inhibitory effect of YopE described in this study revealed a novel function of Yop effector proteins in regulating the inflammatory response against Yersinia infection.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, four of the six injected effectors of Yersinia were believed to target elements of the cytoskeleton to block phagocytosis. However, recent reports illustrated that some of the anti-phagocytic effectors such as YopH can also interfere with signaling pathways of the immune defense system, leading to a down-regulation of the F c -mediated oxidative burst in macrophages and neutrophils, for example (12,46,47). The caspase-1 inhibitory effect of YopE described in this study revealed a novel function of Yop effector proteins in regulating the inflammatory response against Yersinia infection.…”
Section: Discussionmentioning
confidence: 99%
“…Lysates were then mixed with GST fusion protein kinase substrates (2.5 mg of each, as indicated) and gluthathione-sepharose (15 ml, Amersham) and incubated at 48C overnight. Experiments were carried out as described (Ruckdeschel et al, 1997) with two dierent GST fusion protein kinase substrates obtained from M Karin (GST-c-jun (1 ± 222), and B De ridjard (GST-ATF-2). After pull-down, beads were washed four times with binding buer (20 mM HEPES, pH 7.7, 50 mM NaCl, 25 mM MgCl 2 , 0.1 mM EDTA, 0.05% Triton X-100), and in vitro phosphorylation was carried out for at 308C for 20 min in 30 ml of kinase buer containing, 20 mM HEPES, pH 7.6, 20 mM MgCl 2 , 20 mM b-glycerophosphate, 0.1 mM Na 3 VO 4 , 2 mM DTT, 20 mM p-nitrophenylphosphate, 20 mM ATP (4 mCi of [g-32 P]ATP).…”
Section: Cell Culturementioning
confidence: 99%
“…Meanwhile, increasing evidence suggests that bacterial pathogens target and manipulate those signaling pathways for their benefits (12). For example, Yersinia enterocolitica was indicated to suppress TNF production by inhibiting ERK1/2, p38, and JNK activities (13). Macrophages infected with Mycobacterium avium showed decreased MAPK activation compared with the cells infected with nonpathogenic mycobacteria (14).…”
mentioning
confidence: 99%